2022
DOI: 10.1007/s40519-022-01422-6
|View full text |Cite
|
Sign up to set email alerts
|

In silico identification of the rare-coding pathogenic mutations and structural modeling of human NNAT gene associated with anorexia nervosa

Abstract: Purpose Increase susceptibility towards Anorexia nervosa (AN) was reported with reduced levels of NNAT gene. We sought to investigate the most pathogenic rare-coding missense mutations (nsSNPs) of NNAT and their potential damaging impact on protein function through transcript level sequence and structure based in silico approaches. Methods Gene sequence, SNPs of NNAT was retrieved from public databases and the putative post-translational modi cation (PTM) sites were analyzed. Distinctive in silico algorithms w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…This hypothesis is consistent with the findings of Lombardi et al [ 9 ], who linked single nucleotide polymorphisms (SNP) in the Nnat gene to increased susceptibility to AN. Subsequently, a recent in silico study [ 46 ] identified a Nnat SNP missense variant that strongly affects gene expression and is also hypothesized to interact with drugs commonly used in AN therapy, which could lead to implications for treatment efficacy. However, the extent to which the described variants lead to increased or decreased expression of Nnat gene products remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is consistent with the findings of Lombardi et al [ 9 ], who linked single nucleotide polymorphisms (SNP) in the Nnat gene to increased susceptibility to AN. Subsequently, a recent in silico study [ 46 ] identified a Nnat SNP missense variant that strongly affects gene expression and is also hypothesized to interact with drugs commonly used in AN therapy, which could lead to implications for treatment efficacy. However, the extent to which the described variants lead to increased or decreased expression of Nnat gene products remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…DeepView/Swiss-PdbViewer was used for energy minimization of the obtained PDB structure of the Hmgcr gene . The model was validated through PROCHECK stereochemical assessment through an ERRAT quality factor, Ramachandran plot, Prosa-web (), and residual properties of the constructed model. , The dihedral angles φ against ψ of possible conformations of amino acids in protein structure had also been studied in the Ramachandran plot. The SAVES (Structure Validation Server: ) web server was used to know the probable structural errors and z -score. , PDBsum was also used to investigate the protein’s secondary structural details …”
Section: Methodsmentioning
confidence: 99%
“…sbg.ac.at/prosa.php), and residual properties of the constructed model. 23,24 The dihedral angles φ against ψ of possible conformations of amino acids in protein structure had also been studied in the Ramachandran plot. The SAVES (Structure Validation Server: https://saves.mbi.ucla.edu/) web server was used to know the probable structural errors and zscore.…”
Section: Gene's Retrieval and Sequence Alignmentmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, investigators recently sought to investigate the impact of mutations of the well‐recognized Neuronatin (NNAT) gene. Examination of the post‐translational modification (PTM) site was conducted by exploring the effects of structural modifications at NNAT's PTM‐acetylation site (K59) located in the cytoplasmic domain (Azmi et al, 2023). Using trained in silico ML algorithms and consensus classifiers, the research team showed that three structural modifications resulted in the highest structural destabilization and decreased molecular flexibility, which the authors posited could serve as a basis to explore further relationships of risk of AN onset.…”
Section: Exploring Application Of Ai Within the Field Of Eating Disor...mentioning
confidence: 99%